Harta Bawaan Menurut KHI Dan KUHper - Sadi, Azwir Amir (Jurnal El-Thawalib, 2021)
Marriage assets are a very big issue in the life of husband and wife, especially when they divorce so that the marriage law has played an important role in family life even when the marriage is running smoothly. It will be difficult to understand how the continuity of a marriage is if the marriage is not supported by the existence of assets. The problems discussed in this thesis are how the legal status of inherited assets in marriage according to the Compilation of Islamic Law and the Civil Code and how the similarities and differences of property in the Compilation of Islamic Law and the Civil Code. The purpose of this research is to find out how the legal status of the original assets according to the Compilation of Islamic Law and the Civil Code and to find out how the similarities and differences of property in marriage according to the Compilation of Islamic Law and the Civil Code. In this study, researchers used the normative juridical method through the library research method. The normative juridical approach is used in an effort to analyze legal material by referring to legal norms, legal history and doctrine as well as jurisprudence. The results of this study can be concluded that, according to the Compilation of Islamic Law Article 86 and Article 119 of the Civil Code there are similarities and differences in the mixing of assets, Article 86 KHI emphasizes that there is no mixing of assets, while Article 119 of the Civil Code has been carried out since the marriage was carried out, according to the law occurs joint assets, in the agreement to separate assets are both regulated in the KHI and the Civil Code. In the KHI, the assets are under their respective control, while in the Civil Code the control of the assets is the husband and the assets obtained after marriage become joint assets.